Consumers’ intention to adopt last-mile drone delivery services: A comparison between US and Thai consumers - Chen, Charlie; Leon, Steve; Kaewkitipong, Laddawan (Thailand and The World Economy, 2024)
This research explores factors influencing an intention to adopt last-mile drone delivery services in two groups of culturally different countries: Thailand and the USA. Despite the fact that drone raises privacy concerns to consumers, few research has investigated the interplay between perceived usefulness and perceived privacy risks and their effect on the consumers’ intention to adopt last-mile drone delivery services. In addition, no prior research has compared the effect of privacy risks and usefulness on the adoption intention in different national culture. An online survey was distributed to potential consumers of drone delivery services in both countries. PLS-SEM analysis was then conducted to understand the relationships of seven factors within the context of drone delivery service adoption. The results show that consumers from the two countries share similar perceptions towards last mile drone delivery. Perceived usefulness and trust were found the most influential factors on intention to adopt last-mile drone delivery in both groups.